(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
The vulnerability of social networks. Password hints are typically used in conjunction with security questions. When creating a password hint, users should avoid using obvious or easily guessable information. The purpose of a password hint is to help users remember their password without needing to reset it. Password hints are prompts or clues that a user can set up when creating a password for their social network account.